1999
DOI: 10.1046/j.1365-2923.1999.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in medical graduates' assessment of their personal attributes

Abstract: The findings are consistent with current theories which relate to personality differences between men and women and socialization during early upbringing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 10 publications
0
31
0
5
Order By: Relevance
“…In one study, female physicians were found to have more apprehension, less self-assurance, and worried more than their male counterparts. 36 Physician gender is R5 associated with different personality characteristics, 41,42 either innate or learned, and several studies have pointed towards a gender impact on decisionmaking. [43][44][45][46] Gender is generally associated with risktaking behaviour 47 which may explain the finding that missed diagnosis of an acute coronary syndrome in the ED is more likely to happen with a male physician than a female.…”
mentioning
confidence: 99%
“…In one study, female physicians were found to have more apprehension, less self-assurance, and worried more than their male counterparts. 36 Physician gender is R5 associated with different personality characteristics, 41,42 either innate or learned, and several studies have pointed towards a gender impact on decisionmaking. [43][44][45][46] Gender is generally associated with risktaking behaviour 47 which may explain the finding that missed diagnosis of an acute coronary syndrome in the ED is more likely to happen with a male physician than a female.…”
mentioning
confidence: 99%
“…La falta de asociación entre las preferencias IT y el rendimiento, en las mujeres, puede atribuirse a influencias culturales, que asocian ser mujer con una mayor capacidad de comunicarse 24 . Por ello, aun cuando la mujer tenga preferencias IT, es posible que sus habilidades interpersonales estén suficientemente desarrolladas como para desempeñarse en forma satisfactoria en el ámbito interpersonal.…”
Section: Discussionunclassified
“…A paper version of the survey instrument had been used and validated with medical graduates. 16 Participation in the study implied respondents' consent. This study was deemed exempt from review by an institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, however, research conducted on the socialization of health professions students appears inconclusive regarding the development of the psychosocial aspects of patient care practice. 16 No study has yet contrasted pharmacists' self-perceived ability to provide patient care with the respondents' beliefs about the desirability of these attributes. This comparison may reveal a more accurate estimate of an individual's likelihood to assume responsibility for a patient's drug-related needs in the future.…”
Section: Introductionmentioning
confidence: 99%